Arcade on second floor gallery - Ghosh, Ayan (2023)
FW Stevens submitted two colored drawings of his design, one of its exterior and one of the Council Chamber, backing it with convincing arguments. He had visited Europe to study town halls and proposed a well-ventilated building for the municipality. Steven's new design was accepted and he was awarded the project, and Chisholm's proposal was canceled.